Nontraumatic Acute Paraplegia Associated With Cervical Disk Herniation - Liu, Chao (American Paraplegia Society, 2010)
BACKGROUND: Acute paraplegia is a true emergency. It is often the result of trauma but is rarely reported in association with cervical disk herniation in patients without antecedent injury. METHODS: Case report. FINDINGS: This 75-year-old man presented with acute paraplegia due to severe compression of the spinal cord by herniation of the C4-C5 cervical disk. He underwent emergency diskectomy and anterior fusion. Postoperatively, his neurologic functions improved gradually. CONCLUSIONS: Cervical disk herniation should be considered in the differential diagnosis of nontraumatic acute paraplegia. Pre-existing narrowed canal is an important predisposing factor and excessive neck movements are believed to be triggering factors. Immediate early decompressive surgery is recommended to avoid irreversible progression of neurologic deficit.